A decoupling controller by hierarchical backstepping method for straight-line tracking of unmanned surface vehicle. Issue 1 (1st January 2019) - Wang, Chunxin; Xie, Shaorong; Chen, Huizi; Peng, Yan; Zhang, Dan
ABSTRACT: For the straight-line tracking of unmanned surface vehicle (USV), most researchers pay much attention to the course control. In the present work, a strategy of decoupling and control of the speed and yaw of the USV is proposed to maintain a constant speed and a desired course, which ensures the high efficiency of ship-borne sonar during a seabed exploration. Since USV is 3-DOF underactuated system, the Lyapunov direct method is combined with the hierarchical back stepping control method to achieve the desired speed and yaw angle of USV under the external disturbances, such as wind, waves and currents. A disturbance observer is then constructed to compensate the oscillation by predicting changes in external disturbances. The control system is further proved to be asymptotically stable by the Lyapunov theory. The validity and robustness of this decoupling controller is verified by applying to a practical USV in the straight-line tracking.